2018
DOI: 10.18502/kss.v3i3.1896
|View full text |Cite
|
Sign up to set email alerts
|

The Supply Shortage of Accounting Graduates in Indonesia: The Public Accounting Firms Perspective

Abstract: Although having abundant accounting graduates, Indonesia has a very low number of public accountants and accounting firms. This study investigates the difficulties of public accounting firms in Indonesia to recruit accounting staff. Partners or human resource managers from 35 public accounting firms were interviewed, and it was found that the majority of accounting firms facing difficulties in recruiting accounting staff both in quantity and the quality of fresh graduate. Three major problems were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
1
9
0
2
Order By: Relevance
“…Socio-cultural and financial factors produce significant variation in students' careers choice, like those in market economies, enabling money and power when deciding career choice (Agarwala, 2008). Low salary is one of the demotivating factors among Indonesian students to choose an accounting career (Suryani, 2018). Similarly, Omar et al (2015) investigated undergraduate students and found that salary is the most important influencing factor for a student to pursue an accounting career.…”
Section: Financial Rewards (Fr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Socio-cultural and financial factors produce significant variation in students' careers choice, like those in market economies, enabling money and power when deciding career choice (Agarwala, 2008). Low salary is one of the demotivating factors among Indonesian students to choose an accounting career (Suryani, 2018). Similarly, Omar et al (2015) investigated undergraduate students and found that salary is the most important influencing factor for a student to pursue an accounting career.…”
Section: Financial Rewards (Fr)mentioning
confidence: 99%
“…Indeed, the challenge of satisfying the demands of accounting professionals throughout the world could worsen, if urgent steps are not taken to point out the main cause of students not taking accounting majors. In part, low salary, misinformation about workload, and students' negative perception have been acknowledged to be a significant source of this problem (Suryani, 2018).…”
mentioning
confidence: 99%
“…The unemployment rate among university graduates is consistently higher than that of the adult population in many countries, and this has become a new social problem [1]. When viewed from the perspective of university graduates themselves, it is found that while studying in university they learn only basic concepts without further application and this causes them to not be ready for work [2]. This is apart from the problem of mismatch between the skills possessed and the demands of the expected level of work because university graduates tend to lack work experience.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from the OJK or FSA, there are 781 active public accountants [17]. Chairman of the Institutional and Corporate Cooperation Division of the Indonesian Institute of Management Accountants or Institut Akuntan Manajemen Indonesia (IAMI), Haru Koesmahargyo, said that only 1,291 accountants from Indonesia had received the ASEAN Chartered Professional Accountant (ASEAN CPA) certificate [18].…”
Section: Introductionmentioning
confidence: 99%